Contemporary experimental currents and its impact on the structure of the contemporary Iraqi theatrical text "The epic theater as a model" - Haitham Hamza Salman Al-Hamdani (College of Fine Arts / University of Baghdad, 2021)
In this research study, I tried to trace the epic effect to learn how it was understood and how it was used. Following the descriptive and analytical approach in the research, the first chapter dealt with a presentation of the methodological framework of the problem, the goal, the limits of the research, the importance and the need for it and the definition of terms, as well as the theoretical framework which consisted of two topics, including the impact of the epic theater on the world theater and the second the effect of the epic theater on the Arab theater, This came by tracing the epic impact on the world stage of the Greeks, the Middle Ages, the Renaissance, and the Arab theater of the twentieth century. As for the second topic, which deals with the impact of epic theater on the structure of the Arab theatrical text in general and the Iraqi theater in particular, by reviewing some writers who have been affected by this approach. As for the third chapter, it came with the procedures and analysis of the intentional sample in which most of the epic elements were found, which facilitated the task to be achieved and the desired research objectives. The fourth chapter deals with the findings and conclusions as well as the list of sources and references